Comparative transcriptome profiling of the injured zebrafish and mouse hearts identifies miRNA-dependent repair pathways. Issue 1 (7th February 2016) - Crippa, Stefania; Nemir, Mohamed; Ounzain, Samir; Ibberson, Mark; Berthonneche, Corinne; Sarre, Alexandre; Boisset, Gaëlle; Maison, Damien; Harshman, Keith; Xenarios, Ioannis; Diviani, Dario; Schorderet, Daniel; et al.
Abstract: Aims: The adult mammalian heart has poor regenerative capacity. In contrast, the zebrafish heart retains a robust capacity for regeneration into adulthood. These distinct responses are consequences of a differential utilization of evolutionary-conserved gene regulatory networks in the damaged heart. To systematically identify miRNA-dependent networks controlling cardiac repair following injury, we performed comparative gene and miRNA profiling of the cardiac transcriptome in adult mice and zebrafish. Methods and results: Using an integrated approach, we show that 45 miRNA-dependent networks, involved in critical biological pathways, are differentially modulated in the injured zebrafish vs. mouse hearts. We study, more particularly, the miR-26a-dependent response. Therefore, miR-26a is down-regulated in the fish heart after injury, whereas its expression remains constant in the mouse heart. Targets of miR-26a involve activators of the cell cycle and Ezh2, a component of the polycomb repressive complex 2 (PRC2). Importantly, PRC2 exerts repressive functions on negative regulators of the cell cycle. In cultured neonatal cardiomyocytes, inhibition of miR-26a stimulates, therefore, cardiomyocyte proliferation. Accordingly, miR-26a knockdown prolongs the proliferative window of cardiomyocytes in the post-natal mouse heart. Conclusions: This novel strategy identifies a series of miRNAs and associated pathways, in particular miR-26a, which represent attractive therapeutic targets for inducing repair in the injured heart.